Bimbingan Karir Berbasis Konsep Manusia Toraja di Era Revolusi Industri 4.0 - Herman Titting; Feriyanto Feriyanto (Institut Agama Kristen Negeri Toraja, 2021)
This research aims to review human concept-based career guidance in the Context of Toraja to help students in the era of the industrial revolution 4.0. The importance of this research is based on the background of the lack of student-oriented career guidance based on human concepts in its culture. The data is obtained using qualitative methods through literature studies, field observations, and interviews. The data was analyzed with a descriptive qualitative approach with steps according to Creswell, so that it found themes of career guidance based on human concepts in a particular culture. This study concludes that career guidance is very appropriate to be based on human concepts, such as the concept of lolo tau in the context of Toraja to prepare students for the industrial revolution 4.0. Tujuan dari penelitian ini adalah untuk mengkaji bimbingan karir berbasis konsep manusia dalam konteks Toraja untuk membantu siswa di era revolusi industri 4.0. Pentingnya penelitian ini didasarkan pada latarbelakang kurangnya bimbingan karir yang berorientasi pada siswa berdasarkan konsep manusia dalam budayanya. Data diperoleh dengan menggunakan metode kualitatif melalui studi literatur, pengamatan lapangan dan wawancara. Data dianalisis dengan pendekatan kualitatif deskriptif dengan langkah-langkah menurut Creswell, sehingga ditemukan tema-tema bimbingan karir berbasis konsep manusia pada budaya tertentu. Kesimpulan dari penelitian ini adalah bimbingan karir sangatlah tepat untuk dapat didasarkan pada konsep manusia, seperti konsep lolo tau dalam konteks Toraja untuk mempersiapkan siswa menghadapi revolusi industri 4.0.